Mathematical modelling of wave overtopping at vertical structures - Fadhlyya Arawaney, Abdul Ghani; Mohd Shahridwan, Ramli; Nor Aida Zuraimi, Md Noar; Abdul Rahman, Mohd Kasim (IOP Publishing, 2019)
Considering the threats of wave overtopping that can cause flooding in the coastal area and hence implying various damages to the inland properties, this paper provides a simplified mathematical modelling of wave overtopping calculation at vertical seawall as proposed by Cooker. Taking the assumption that the water jet particles projected against the seawall move as free projectiles, a simple estimation is made from the computation of the water displacement which can pass over top of the wall of finite height by applying the trapezoidal rule to the equations derived from both energy conservation and the pressure impulse, P previously proposed by Cooker. The results indicate that the overtopping volume per wave is exponentially decaying with the height of the wall above the still water level and is in good agreement to previous researcher and is used to estimate the overtopping discharge for berm and ditch structures. Both cases are comparable for corresponding freeboard values which concluded that the water jet onto the seawall with berm structure will reach higher in the air compared to that of with ditch.